Ten Rules You Absolutely Must Not Break If You Want to Survive the School Bus - Grandits, John; 1965-; Austin, Michael (New York, 2011)
Before Kyle rides a school bus for the first time, his older brother gives him a list of rules he must follow but after breaking every single one the first day, Kyle discovers the rule his brother left out.
Keywords: Transportation; Fiction; Brothers; Fiction; School children; Humorous fiction; School stories